Blockchain's potential in forest offsets, the voluntary carbon markets and REDD+. (18th September 2022) - Kotsialou, Grammateia; Kuralbayeva, Karlygash; Laing, Timothy
Summary: Increasing net-zero commitments by individuals, companies and governments have been accompanied by the growth of the voluntary offset market, including Reducing Emissions from Deforestation and Forest Degradation (REDD+). Technologies, notably blockchain, are starting to enter the REDD+ space and may have the potential to address issues such as additionality, permanence, leakage and property and community rights. In this Perspective, we first examine voluntary markets and the role forest carbon offsets have played within them, highlighting the evolution of REDD+ and the issues that have hindered its development. We then examine the potential of blockchain to address each of the issues, using the literature and emerging experience from the use of blockchain in the forestry space. We find that the technology may have the potential to improve verifiability, reduce transaction costs and, to a lesser degree, aid in addressing additionality and permanence concerns. However, greater learning from the emerging use of blockchain in pilot projects is needed to fully assess and maximize its potential.